Expanding Indications for Flow Diverters: Distal Aneurysms, Bifurcation Aneurysms, Small Aneurysms, Previously Coiled Aneurysms and Clipped Aneurysms, and Carotid Cavernous Fistulas. (16th December 2019) - Limbucci, Nicola; Leone, Giuseppe; Renieri, Leonardo; Nappini, Sergio; Cagnazzo, Federico; Laiso, Antonio; Muto, Mario; Mangiafico, Salvatore
Abstract: Flow diverter devices have gained wide acceptance for the treatment of unruptured intracranial aneurysms. Most studies are based on the treatment of large aneurysms harboring on the carotid syphon. However, during the last years the "off-label" use of these stents has widely grown up even if not supported by randomized studies. This review examines the relevant literature concerning "off-label" indications for flow diverter devices, such as for distal aneurysms, bifurcation aneurysms, small aneurysms, recurrent aneurysms, and direct carotid cavernous fistulas.